2006
DOI: 10.1007/s00442-006-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

Root controls on soil microbial community structure in forest soils

Abstract: We assessed microbial community composition as a function of altered above- and belowground inputs to soil in forest ecosystems of Oregon, Pennsylvania, and Hungary as part of a larger Detritus Input and Removal Treatment (DIRT) experiment. DIRT plots, which include root trenching, aboveground litter exclusion, and doubling of litter inputs, have been established in forested ecosystems in the US and Europe that vary with respect to dominant tree species, soil C content, N deposition rate, and soil type. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 45 publications
12
102
2
Order By: Relevance
“…Because fragmentation increases litter decomposability (David and Handa 2010;Hassall et al 1987), this might have led to a flush of available C and nutrients, which could have supported fast-growing bacteria and led to increased concentrations of bacterial PLFAs at the first sampling. In the long term, however, we did not find any influence of litter removal on the contribution of fungi to the soil microbial community, which refutes hypothesis v. This is in line with a study of Brant et al (2006), which studied the influence of aboveand below-ground litter manipulation on soil microorganisms at 3 different sites in the USA and H u n g a r y. T h e y r e p o r t e d n o i n f l u e n c e o f aboveground litter removal after 4, 7 and 13 years, respectively. Similar to our results, Creamer et al (2015) reported that bacterial community composition analysed by terminal restriction fragment length polymorphism (T-RFLP) was not different in mineral soils compared to mineral soils mixed with preincubated eucalyptus litter.…”
Section: Soil Microbial Community Compositionsupporting
confidence: 92%
“…Because fragmentation increases litter decomposability (David and Handa 2010;Hassall et al 1987), this might have led to a flush of available C and nutrients, which could have supported fast-growing bacteria and led to increased concentrations of bacterial PLFAs at the first sampling. In the long term, however, we did not find any influence of litter removal on the contribution of fungi to the soil microbial community, which refutes hypothesis v. This is in line with a study of Brant et al (2006), which studied the influence of aboveand below-ground litter manipulation on soil microorganisms at 3 different sites in the USA and H u n g a r y. T h e y r e p o r t e d n o i n f l u e n c e o f aboveground litter removal after 4, 7 and 13 years, respectively. Similar to our results, Creamer et al (2015) reported that bacterial community composition analysed by terminal restriction fragment length polymorphism (T-RFLP) was not different in mineral soils compared to mineral soils mixed with preincubated eucalyptus litter.…”
Section: Soil Microbial Community Compositionsupporting
confidence: 92%
“…2). Brant et al (2006) also observed an increase in bacteria in mineral soils four months after trenching. Similar to our findings, the change was not evident any more ten months after trenching.…”
Section: Discussionmentioning
confidence: 66%
“…Trenching immediately disrupts the supply of recent photosynthates to the roots and mycorrhiza. Especially mycorrhizal fungi and associated bacteria will suffer from the lack of labile C. Soil microbial community composition may change and thereby alter the decomposition rates on trenched plots (Brant et al 2006;Hanson et al 2000;Kuzyakov 2006). Since autotrophic soil respiration includes mycorrhizal respiration, the breakdown of mycorrhizal respiration is anticipated in order to separate the autotrophic fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that the net primary productivity (NPP) in TRH is lower than that in other places of the world (Cramer et al, 1999;Sun et al, 2013b;Yuan et al, 2014). Considering the essential roles of the substrates from the plants to microorganisms, the low NPP would fundamentally limit the abundance of microbes in TRH (Brant et al, 2006;Fierer et al, 2009;Zak et al, 1994). Thus, soil microbial biomass should positively correlate with total soil organic carbon content and belowground plant biomass.…”
Section: Soil Microbial Biomass C and N In Trhmentioning
confidence: 99%